An exploratory study of the key determinants of self-referral by women in labour to Chris Hani Baragwanath Hospital in the Johannesburg Metro District, South Africa - Kula, Nonkqubela Carvie (Department of Paediatrics and Child Health, 2018)
Introduction: At Chris Hani Baragwanath Hospital (CHBH) in Johannesburg overcrowding remains a concern as women who have low-risk pregnancies continue to bypass community-based obstetric facilities to deliver at the tertiary hospital. A significant number of self-referred pregnant women had no obstetric risk factors qualifying them for delivery at CHBH Maternity Unit. The primary concern at CHBH was that the management of low-risk maternity patients in high-risk a setting interfered with the care of patients requiring specialist care. Study Objectives: To determine the socio-demographic characteristics of the women who selfrefer to CHBH; to explore the reasons why low-risk patients present at CHB Maternity Hospital in labour, and to determine obstetric risk factors amongst self- referred pregnant women. Methods: A descriptive, cross-sectional study was conducted focusing on self-referred pregnant women who delivered at CHBH and were in the post-natal ward during the study period (26 October 2013 to 03 November 2013). A structured questionnaire was administered by the researcher to each study participant to establish variables of the key determinants of self-referral. The data were analyzed using SPSS version 18 and all tests for statistical significance between appropriate and inappropriate self-referral were carried out at a p=0.05 level of significance with a 95% confidence interval. Results: The total number of deliveries for the study period 26 October 2013 to 3 November 2013 was 514 of which 112 were self-referrals. Only 108 women consented to participate in the study and were subsequently interviewed. The results indicated that of the pregnant women who self-referred to CHBH for delivery (N=108), 58.33% travelled more than 5km, 14,81% were teenagers, 81.48% were single, only 1.85% had no formal education, while 72.22% were unemployed. The results further showed that 47.22% of the women had a history of obstetric risk factors and were appropriate for delivery at CHBH, while the majority (52.78%) were low-risk pregnancies and should have delivered at local MOUs. Analysis of the results showed that age (p=0.042), transport mode (p=0.030), transport cost (p=0.001), transport ownership (p=0.041), distance (p=0.032) and waiting times (p=0.025) had statistically significant influence on self-referral. 22.22% were of the high-risk age-groups (<20 years and >35 years), 2,78% had previous surgery, and 12.04% had medical conditions for which they were on treatment. Conclusion: This study showed that the referral system for maternity care within the Johannesburg Metro Health District is not fully functional. Most of selfreferrals were inappropriate for CHBH. The age of the pregnant woman, transport, distance and waiting times at the service point are key determinants of self-referral.